Evaluating a sexual violence primary prevention program in Australian secondary schools: A protocol for a pilot cluster randomised controlled trial - Freda Haylett; Jacqueline Kuruppu; Jessica Ison; Jacqui Theobald; Gabriel Caluzzi; Xia Li; Innocent Mwatsiya; Sarah Vrankovich; Kerryn O’Rourke; Adam Bourne; Kirsty Forsdike; Nicola Henry; et al. (PLoS ONE, 2026)
Background Sexual violence is a global human rights issue and a significant public health concern. Prevention of sexual violence requires addressing the structural and social norms that perpetuate it. Schools are promising settings for primary prevention interventions, as early socialisation experiences can shape attitudes and behaviours that enable sexual violence. However, evidence on effective school-based interventions is limited. The objective of this pilot study is to assess the feasibility and preliminary effectiveness of an Australian sexual violence primary prevention program, the Schools Education Program, on student sexual violence knowledge, attitudes and behavioural intentions. Methods/design A two-arm, parallel pilot cluster randomised controlled trial will be conducted with Year 9 students (aged 13–15) in 12 secondary schools across one Australian state. Ten schools will be randomly allocated to the SEP intervention (n = 6) or a waitlist control (n = 4); an additional two schools are pre-assigned to the waitlist control group. The SEP comprises three student education modules, parent and staff education, and the recruitment of School Student Champions. The primary outcome is sexual violence knowledge. Secondary outcomes include attitudes, behavioural intentions, and implementation factors. Quantitative data will be collected at baseline, immediately post-intervention, and at 6-month follow-up. Analysis will use linear mixed-effects models to provide preliminary estimates of effect and estimate key parameters for a future definitive trial. The trial is embedded within a concurrent realist evaluation that includes qualitative methods to explore the mechanisms and contextual conditions shaping these outcomes. Discussion This study is the first pilot trial to evaluate a sexual violence primary prevention intervention in Australian secondary schools. In addition to the trial focused on sexual violence prevention outcomes, its integration with realist evaluation methodology will advance knowledge about how, when, and for whom these outcomes occur. The study findings will inform adaptability and scalability for secondary schools nationally and internationally. Trial registration The trial is prospectively registered with the Australian and New Zealand Clinical Trials Registry (reference: ACTRN12625000409471p). Registered 6 May 2025. Protocol version v.1.0, 20/05/2025